Metadiscourse Features in the Persuasive Essays of Undergraduate Writers - Tan, Helen (2011)
Metadiscourse is a useful linguistic resource for writers, particularly, in the writing of a persuasive essay. Its usefulness is two-pronged. It guides readers through the text, and it provides the writers the tool to engage with their readers. It has been acknowledged by writing researchers that a successful employment of metadiscourse will mark writing efficacy. However, L2 writers tend to have difficulties in using such linguistics features in their writing. To understand the nature of the use of metadiscourse, and therefore the problems associated with its use, this study investigated the use of metadiscourse by a group of high and low English language proficiency (hereafter refer to as HEP and LEP) undergraduate writers. Using a concordance software, MP2.2, the metadiscourse use of the HEP and LEP Malaysian undergraduate writers was compared and contrasted for their frequency (per 10000 words) and forms of use. In addition, the HEP undergraduate writers’ use of metadiscourse was also compared with that of a standard learner corpus [British Academic Written English (BAWE)]. In addition, a quasi experiment was carried out to determine the effect of instructional input on the use of metadiscourse by the undergraduate writers. The data revealed that between the HEP and LEP undergraduate writers, the HEP writers demonstrated a higher frequency and more varied forms of use of both the interactive and interactional metadiscourse. Both groups of writers, however, preferred the use of interactional metadiscourse rather than the interactive. This suggested that they were more concerned with the building of writer-reader relationships. When the HEP writers’ use of metadiscourse was reviewed against that of the BAWE corpus, some differences in their use of metadiscourse were exhibited. The frequency of metadiscourse use in the BAWE corpus was higher, and their forms of metadiscourse use were also much more varied than the HEP writers. The BAWE corpus writers’ also used more interactive metadiscourse than interactional metadiscourse. Conversely, the HEP writers showed a greater preference for interactional metadiscourse. The effect of instructional input on metadiscourse use of an intact group of undergraduate writers, however, was found to be insignificant. One possible reason could be that the sample size was small. In addition, the short duration of instructional input (12 hours) may not be adequate for them to cognitively process and acquire all the ten different subcategories of metadiscourse to show improvement. Nonetheless, the cross tabulation of the data indicated that the instructional input had benefited some LEP participants to some extent. A qualitative analysis also indicated that some HEP [British Academic Written English (BAWE)]. In addition, a quasi experiment was carried out to determine the effect of instructional input on the use of metadiscourse by the undergraduate writers. The data revealed that between the HEP and LEP undergraduate writers, the HEP writers demonstrated a higher frequency and more varied forms of use of both the interactive and interactional metadiscourse. Both groups of writers, however, preferred the use of interactional metadiscourse rather than the interactive. This suggested that they were more concerned with the building of writer-reader relationships. When the HEP writers’ use of metadiscourse was reviewed against that of the BAWE corpus, some differences in their use of metadiscourse were exhibited. The frequency of metadiscourse use in the BAWE corpus was higher, and their forms of metadiscourse use were also much more varied than the HEP writers. The BAWE corpus writers’ also used more interactive metadiscourse than interactional metadiscourse. Conversely, the HEP writers showed a greater preference for interactional metadiscourse. The effect of instructional input on metadiscourse use of an intact group of undergraduate writers, however, was found to be insignificant. One possible reason could be that the sample size was small. In addition, the short duration of instructional input (12 hours) may not be adequate for them to cognitively process and acquire all the ten different subcategories of metadiscourse to show improvement. Nonetheless, the cross tabulation of the data indicated that the instructional input had benefited some LEP participants to some extent. A qualitative analysis also indicated that some HEP and LEP writers did improve in their awareness of the use of metadiscourse in their post writing. Generally, there was more employment of metadiscourse in the post writing when compared with the pre writing. In addition, the post writing also saw a greater awareness on the appropriate use of metadiscourse. They were in the use of endophoric markers, transitions and frame markers. The data also indicated that the use of evidentials is a major problem among the undergraduate writers, even among those who showed positive improvement in their post writing. In conclusion, this study demonstrated that the undergraduate writers’ use of metadiscourse was still at an evolving stage. It is imperative that the awareness of the important use of metadiscourse in academic writing among the undergraduates’ writers be further heightened in writing classrooms. However, this has to be done over time, with the provision of graded tasks on the learning of metadiscourse use (from the simple to the most difficult) in writing programmes. Besides this important pedagogical implication, the concordance software has generated a useful display of the nature of metadiscourse use, and it is suggested that the output could serve as an effective authentic instructional input in the learning of metadiscourse. This useful instructional resource would benefit both the ESL practitioners and learners alike.